Ambulance referral for emergency obstetric care in remote settings. Issue 3 (June 2016) - Tsegaye, Ademe; Somigliana, Edgardo; Alemayehu, Tadesse; Calia, Federico; Maroli, Massimo; Barban, Paola; Manenti, Fabio; Putoto, Giovanni; Accorsi, Sandro
Abstract: Objective: To evaluate the functionality of an ambulance service dedicated to emergency obstetric care (EmOC) that referred pregnant women to health centers for delivery assistance or to a hospital for the management of obstetric complications. Methods: A retrospective study investigated an ambulance referral system for EmOC in a rural area of Ethiopia between July 1 and December 31, 2013. The service was available 24 h a day and was free of charge. Women requesting referral were transported to nearby health centers. Assistance was provided locally for uncomplicated deliveries. Women with obstetric complications were referred from health centers to a hospital. Results: A total of 528 ambulance referrals were recorded. The majority of patients (314 [59.5%]) were transported from villages to health centers. The remaining individuals were brought to a hospital, having been referred from health centers (179 [33.9%]) or were referred directly from villages owing to hospital proximity (35 [6.6%]). Of the 179 patients referred to the hospital from health centers, 84 (46.9%) were diagnosed with major direct obstetric complications. No maternal deaths were recorded among patients using the ambulance service. The cost of the ambulance service was US 18.47 per referred patient. Conclusions: An ambulance service dedicated to EmOC that interconnected health centers and a hospital facilitated referrals and better utilized local resources.